2016
DOI: 10.1111/bju.13208
|View full text |Cite
|
Sign up to set email alerts
|

Penis cancer management: insight into the future

Abstract: The report of Jakobson et al. [1] assesses the results of the sentinel node procedure for penis carcinoma in Denmark. The sentinel node procedure was done in four university hospitals. In this geographically small country with little more than 5.6 million inhabitants and a case load of 50 patients with penis cancer per year, a distribution of care of patients with penis cancer over four hospitals seems reasonable at first sight.The results show interesting elements. With a false-negative rate of 10.8%, the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Interestingly, we found that the proportion of patients who died of PSCC has increased significantly in recent years, and the proportion has exceeded that of the non‐cancer disease for the calendar of 2012–2017 (Table 3). Several previous studies pointed out that the tumor stage of PSCC was one of the most crucial prognostic factors 11,15,24–26 . For instance, patients with a metastasizing malignant tumor were accompanying distinctly shorter survival time and higher recurrence rate 25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found that the proportion of patients who died of PSCC has increased significantly in recent years, and the proportion has exceeded that of the non‐cancer disease for the calendar of 2012–2017 (Table 3). Several previous studies pointed out that the tumor stage of PSCC was one of the most crucial prognostic factors 11,15,24–26 . For instance, patients with a metastasizing malignant tumor were accompanying distinctly shorter survival time and higher recurrence rate 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…prognostic factors. 11,15,[24][25][26] For instance, patients with a metastasizing malignant tumor were accompanying distinctly shorter survival time and higher recurrence rate. 25,26 In this study, the percentage of PSCC patients classified with localized stage were shown a decline ranging from 65.08% to 52.76% for the calendar of 1992-2001 and 2012-2017, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A noter qu'en cas de positivité du ganglion sentinelle une lymphadenectomie inguinale totale est recommandée du côté pN+ et une lymphadenectomie superficielle du côté pN0.Le curage inguinal modifie ́ est définit par la réalisation d'un curage concerne les quadrants supérieur et central [autour de la veine saphène] chez les patients cN0 a ̀ risque[27].…”
unclassified